2012
DOI: 10.1093/ndt/gfs515
|View full text |Cite
|
Sign up to set email alerts
|

Effect of single-dose rituximab on steroid-dependent minimal-change nephrotic syndrome in adults

Abstract: Our results revealed that rituximab therapy was associated with a reduction in the number of relapses and in the total dose of PSL needed. Therefore, rituximab appears to be a useful therapeutic agent for adult patients with steroid-dependent MCNS. These results suggest that this treatment is rational and should be considered as an important option in the management of adult patients with steroid-dependent MCNS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
72
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 23 publications
5
72
0
3
Order By: Relevance
“…26 The pathogenic role of B lymphocytes would also explain why MCD or FSGS may occasionally occur in patients with other B cell-mediated diseases 27 and why NS remission achieved by rituximab associates with circulating B-cell depletion. [8][9][10][11][12][13][14]26 In patients in this study, persistence of remission after B lymphocyte reappearance in the circulation could actually be the result of a complete and definitive disruption of the potential autoreactive clone(s). This is in line with the evidence that in IMN, persistent remission achieved by rituximab therapy is paralleled by depletion of nephritogenic autoantibodies, even after re-emergence of B lymphocytes in the circulation.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…26 The pathogenic role of B lymphocytes would also explain why MCD or FSGS may occasionally occur in patients with other B cell-mediated diseases 27 and why NS remission achieved by rituximab associates with circulating B-cell depletion. [8][9][10][11][12][13][14]26 In patients in this study, persistence of remission after B lymphocyte reappearance in the circulation could actually be the result of a complete and definitive disruption of the potential autoreactive clone(s). This is in line with the evidence that in IMN, persistent remission achieved by rituximab therapy is paralleled by depletion of nephritogenic autoantibodies, even after re-emergence of B lymphocytes in the circulation.…”
Section: Discussionmentioning
confidence: 77%
“…After the first occasional observation 7 and small uncontrolled studies suggesting the efficacy of B-lymphocyte depletion in children with MCD, 8,9,11-13 a recent observational study suggested that rituximab therapy may reduce the incidence of recurrences in adults with the same disease. 14 Within the limitation of the small sample size, comparative analyses according to patient age either at inclusion or at disease onset suggest that rituximab treatment may be equally effective in children and adults, independent of the underlying pathology. On the other hand, our present data convey the fully novel and clinically relevant message that rituximab may be uniformly effective in patients with steroid-sensitive idiopathic FSGS, regardless of age, which has major clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These initial findings were corroborated by a number of other case reports and retrospective and prospective studies (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Rituximab generally induced sustained remission allowing for a marked reduction or discontinuation of corticosteroids and/or immunosuppressive drugs in patients with MCD who were steroid dependent or frequent relapsers (24).…”
Section: Discussion Of Casementioning
confidence: 57%
“…Rituximab generally induced sustained remission allowing for a marked reduction or discontinuation of corticosteroids and/or immunosuppressive drugs in patients with MCD who were steroid dependent or frequent relapsers (24). Rituximab appears to be more effective when given to patients in complete remission, but a few nephrotic patients also responded (18). It also appears to be beneficial to patients who are steroid resistant (10,11,25).…”
Section: Discussion Of Casementioning
confidence: 99%